2022
DOI: 10.3390/ani12243547
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Eosinopenia as a SIRS Biomarker in Critically Ill Horses

Abstract: Systemic inflammatory response syndrome (SIRS) is a very common finding in critically ill patients. To accurately identify patients with SIRS and those who need intensive care, several markers have been evaluated, including cortisol, WBC or lactate. It is widely known that a stress leukogram includes eosinopenia as one of its main markers (neutrophilia, eosinopenia, lymphopenia and mild monocytes). It is known that cortisol concentration in plasma is the main stress biomarker and is strongly correlated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Eosinophilia in horses is related to allergic airway disease, gastrointestinal helminth infections, allergic skin disease, multisystemic eosinophilic epitheliotropic disease, eosinophilic disease confined to the intestine, phycomycosis, and neoplasia [ 37 ]. Recently, the prognosis of eosinopenia as a biomarker in critically ill horses was described for the first time [ 3 ]. According to this result and those shown in human patients with gastrointestinal diseases, we found that EC in equids with acute abdominal pain are also lower in non-surviving patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Eosinophilia in horses is related to allergic airway disease, gastrointestinal helminth infections, allergic skin disease, multisystemic eosinophilic epitheliotropic disease, eosinophilic disease confined to the intestine, phycomycosis, and neoplasia [ 37 ]. Recently, the prognosis of eosinopenia as a biomarker in critically ill horses was described for the first time [ 3 ]. According to this result and those shown in human patients with gastrointestinal diseases, we found that EC in equids with acute abdominal pain are also lower in non-surviving patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol is the main stress biomarker, which is also strongly correlated with the severity of gastrointestinal disease in horses [ 2 , 3 ]. In horses with colic, cortisol measurement is a very useful marker of illness and severity, as acute abdominal pain leads to sympathetic nervous system activation [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations